ln(x+4)-ln(x-2)=2

Simple and best practice solution for ln(x+4)-ln(x-2)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x+4)-ln(x-2)=2 equation:


Simplifying
ln(x + 4) + -1ln(x + -2) = 2

Reorder the terms:
ln(4 + x) + -1ln(x + -2) = 2
(4 * ln + x * ln) + -1ln(x + -2) = 2
(4ln + lnx) + -1ln(x + -2) = 2

Reorder the terms:
4ln + lnx + -1ln(-2 + x) = 2
4ln + lnx + (-2 * -1ln + x * -1ln) = 2
4ln + lnx + (2ln + -1lnx) = 2

Reorder the terms:
4ln + 2ln + lnx + -1lnx = 2

Combine like terms: 4ln + 2ln = 6ln
6ln + lnx + -1lnx = 2

Combine like terms: lnx + -1lnx = 0
6ln + 0 = 2
6ln = 2

Solving
6ln = 2

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Divide each side by '6n'.
l = 0.3333333333n-1

Simplifying
l = 0.3333333333n-1

See similar equations:

| 3x+30+27y=0 | | -6(w+1)-w-12=-7(w+4)+10 | | -3(a+8)=a+2(5a-7) | | 20+5x=150 | | 4m+45=61+2m | | I=Crt | | 4-5x=39 | | 4s+20=200 | | -10p-5(4-4p)=6(p-2)-16 | | 5p+7p=72 | | 7+8=28+x | | 0.39=log(x) | | 6x-4=14x-42 | | 48-9x=-27+6 | | 6x-4=14-42 | | 9-4m=m^2-n | | 58-9x=-27+6x | | 6(s-3)=10-2(s+2) | | 2n+5+2n=8n+3-2n | | (14+10)x(3+4)= | | 9x-10+14=-8x-5 | | 81x^4=81x^2 | | 4x+5=-72x+81 | | 9x+2y+17+10x-12y-11= | | 63.00+x=67.40 | | 9x-2*(-5+7)=-8x-5 | | -4(4n+3)=8 | | 3x-6+2=5x-6 | | 3x=26.25 | | 5(x+4)=3(2x-1) | | .7(.1x+.1)=-.7 | | 14(v+2)-2v=4(3v+3)-18 |

Equations solver categories